Caregiver daily impression could reflect illness latency and severity in frail elderly residents in long‐term care facilities: A pilot study. Issue 5 (4th June 2015) - Ae, Ryusuke; Kojo, Takao; Okayama, Masanobu; Tsuboi, Satoshi; Makino, Nobuko; Kotani, Kazuhiko; Aoyama, Yasuko; Nakamura, Yosikazu
Abstract : Aims: To propose a caregiver daily impression (CDI) rating instrument for personal caregivers of residents living in long‐term care facilities (LTCF) to comprehensively evaluate residents' daily health condition, and to investigate whether the CDI reflects illness latency and severity in residents transferred emergently. Methods: We carried out a retrospective review of facility care records from 20 LTCF in Hyogo, Japan. The participants were 169 LTCF residents with episodes of transfer to emergency hospitalization facilities during a 3‐month period. We determined specific CDI variables by interviewing experienced LTCF caregivers, and then carried out a principal component analysis to determine the major parameter set. The generated components were incorporated into a regression model to investigate the association with hospitalization. Results: The mean age was 87.9 ± 6.5 years, 68% were women and 28% of transfers resulted in hospitalization. The interview procedure identified 12 specific CDI variables, and the principal component analysis generated five distinct components: "change in feeding, " "change in emotion, " "disengaged or listless gaze, " "decrease in eye reactivity" and "change in movement." By multivariate logistic regression, hospitalization was associated with "decrease in eye reactivity" (adjusted OR 1.78, 95% CI 1.07–2.97) and poor vital signs (adjusted OR 2.84, 95% CI 1.15–6.98), but not with body temperature (adjusted OR 1.29, 95% CI 0.52–3.21). Conclusions: The CDI might reflect underlying illness severity beyond quantitative physical findings. Once the CDI can be appropriately validated, quantified and linked to physical findings, it could be used by caregivers for daily resident assessments and as a practical triage tool in emergency situations.Geriatr Gerontol Int 2016; 16: 612–617.